Analysis of Interest in Physical Activities of Pucang Boyolali Residents in the New Order - Erik Adhi Sulistyo; Pungki Indarto (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
The purpose of this study was to determine how the interest in physical activity in the new order and the factors that influence it. This research is quantitative descriptive. The method used is a survey method with data collection techniques using questionnaires, interviews, observation and documentation. The population used is the residents of Dukuh Pucang Boyolali and uses a sample of all members of the youth organization who are in their teens and adults totaling 53 people. The number of samples of adolescent age is 16 people, while the number of samples of adult age is 37 people. Interest indicators used in this research are awareness indicators, desire indicators and needs indicators. The results of this study are that the interest in physical activity of the residents of Dukuh Pucang Boyolali in the new new order still needs to be improved. Overall residents of Dukuh Pucang Boyolali who have an interest in physical activity with a high category of 15%, while residents with an interest in moderate physical activity are 60%, and residents who have a low interest in physical activity are 25%. The average physical activity intensity of Dukuh Pucang Boyolali residents is 2 times a week with an average time of 55 minutes per week. Factors that influence the physical activity of Dukuh Pucang Boyolali residents are 72% job factor, 15% age factor and 13% environmental factor.